VD_FINDINFO HC / 2022 / 314 vom 25. April 2022 - VD Tribunal cantonal (2022)
CONDITION DE RECEVABILITÉ, LÉGITIMATION ACTIVE ET PASSIVE, INTÉRÊT DIGNE DE PROTECTION | 308 CPC (CH), 59 al. 2 let. a CPC (CH), 59 al. 2 let. c CPC (CH), 60 CPC (CH)